Scleral prosthesis - Namika Sokhal; Salil Pawah; Amit Gupta; Chetan Pathak (Wolters Kluwer Medknow Publications, 2019)
The special sensory organs play a significant role in our daily lives. The disfigurement from loss of facial structure such as eye can cause psychological and social distress. Phthisis bulbi is an ocular condition caused by wound healing secondary to severe trauma, inflammation, or necrotizing tumor of the eye. Eye prosthesis is the only mode of rehabilitation for missing eye if reconstructive surgery is not possible or desired by a patient. Prefabricated eye or customized ocular prosthesis has their own advantages or disadvantages. Prosthetic rehabilitation of such patients is challenging, and multidisciplinary approach is required to provide satisfactory ocular prosthesis. This article presents a technique for fabrication of semicustomized prosthesis with stock iris and custom-made sclera.